Carabodes (Carabodes) labyrinthicus - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Carabodes (Carabodes) labyrinthicus (Michael, 1879) Material – One specimen in Çiftlik Village Tekçam Area, Taşköprü forest, N 41° 14′ 39.56′′, E 34° 12′ 19.57′′, alt. = 1422 m, 15 May 2018; one individual in Alasökü Village, Taşköprü forest, N 41° 20′ 09.64′′, E 34° 25′ 58.98′′, alt. = 1327 m, 10 June 2018, tree bark and debris of P. nigra . Previous record in Turkey – Bolu (Toluk and Ayyildiz 2016). Global distribution – Holarctic. Ecology – Forest soils, moss, litter, tree bark and canopy.

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 261, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Arthropoda; Arachnida; Animalia; Carabodes labyrinthicus; Biodiversity; Sarcoptiformes; Carabodes; Taxonomy; Carabodidae; 15. Life on land